Tourism as a pathway for RES utilisation - Kulišić, Biljana, ekonomistica (Array, 2008)
Abstract: Tourism, due its property of being an “invisible export” sector, has a strong multiplier effect over the economy. Tourists boost demand for numerous goods and services, one of them being energy. Unfortunately, energy sources are scarce for most of the countries in the region. Thus, one could think of another solution to the excess demand for energy than import. Namely, for more than a decade, renewable energy sources are in the central focus of the EU energy policy with an aim to ensure security, price stability, availably and affordability of energy to its citizens together with reduction of GHG emissions and making the EU economy more competitive. Combining tourism with renewable energy sources utilisation helps reducing the spill over effect from energy import. In this paper, the cross-section analysis based on environmental determination of tourism and renewable energy sources potentials is performed in order to indicate a pathway for implementation of renewable energy sources utilisation in the tourism and hotel industry